Inovasi Bupati di Ruang Demokrasi: Upaya Membangun Kesadaran Inovasi Birokrasi - Bambang Widiyahseno (Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
Decentralization and granting broad autonomy to the local government open the space for the continuity ofpolicy innovation. This study is important because not all regional heads could do it. There are many partiesinvolved and interested in the process. This study explores the behavior of regents to build awareness andmindset (unfreezing) to various parties. The magnitude of opportunities to innovate is largely determinedby regent ability to perform the process of unfreezing. The ﬁ ndings indicate a regent’s eﬀ ort in buildingrelationships with various parties, especially the power of the bureaucracy, parliament and society (thepublic) in the process of unfreezing ie melting of the ice or the awareness of the need for change (innovation). Those are Strategies to encourage and initiate innovation to anticipate the bureaucracy, which is building a coalition with the community to deal with the inert bureaucracy.